2003
DOI: 10.1126/science.1083695
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Phospholipid Signaling by GLABRA2 in Root-Hair Pattern Formation

Abstract: The root-hair pattern of Arabidopsis is determined through a regulatory circuit composed of transcription factor genes. The homeobox gene GLABRA2 (GL2) has been considered a key component, acting farthest downstream in this regulation. GL2 modified to include a transactivating function caused epidermal cells to develop ectopic root hairs or root hair-like structures. With this system, the phospholipase Dzeta1 gene (AtPLDzeta1) was identified as a direct target of GL2. Inducible expression of AtPLDzeta1 promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
227
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(234 citation statements)
references
References 19 publications
4
227
2
1
Order By: Relevance
“…A connection between choline content and root hair elongation was also suggested following the mutation of PLDz1, an enzyme responsible for the degradation of PtdCho into PA and choline (Qin and Wang, 2002;Ohashi et al, 2003). However, the double KO pldz1 pldz2 contradicted these results since it did not exhibit any root hair alteration (Li et al, 2006).…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…A connection between choline content and root hair elongation was also suggested following the mutation of PLDz1, an enzyme responsible for the degradation of PtdCho into PA and choline (Qin and Wang, 2002;Ohashi et al, 2003). However, the double KO pldz1 pldz2 contradicted these results since it did not exhibit any root hair alteration (Li et al, 2006).…”
Section: Discussioncontrasting
confidence: 41%
“…Previous studies have reported altered root architecture and epidermal cell death in a XIPOTL1/PEAMT1 KO mutant (xpl1; Cruz-Ramírez et al, 2004). However, even though PCho content was effectively diminished in this mutant, the described phenotype was more likely caused by an impaired balance of choline, PtdCho, and phosphatidic acid (Cruz-Ramírez et al, 2004; AlatorreCobos et al, 2012).A connection between choline content and root hair elongation was also suggested following the mutation of PLDz1, an enzyme responsible for the degradation of PtdCho into PA and choline (Qin and Wang, 2002;Ohashi et al, 2003). However, the double KO pldz1 pldz2 contradicted these results since it did not exhibit any root hair alteration (Li et al, 2006).…”
mentioning
confidence: 99%
“…Phospholipase D (PLD), which cleaves phospholipids to produce phosphatidic acid (PA) and a free head group such as choline, has been implicated in root hair growth and patterning (Ohashi et al, 2003). Ohashi and coworkers also imply that PLD and its product, PA, play a role in root elongation (Ohashi et al, 2003).…”
mentioning
confidence: 99%
“…The cellular level of PA is increased under various stress conditions, such as treatments of abscisic acid (ABA) (4), osmotic stress (5-7), oxidative stress (8), pathogen infection (9,10), and cold and freezing conditions (11)(12)(13). In addition, PA is involved in regulating normal plant growth and development, particularly in roots (14,15) and pollen tubes (16,17).…”
mentioning
confidence: 99%